Pengaruh Kepemilikan Manajerial, Profitabilitas, Free Cash Flow Dan Ukuran Perusahaan Terhadap Manajemen Laba (Studi Pada SubSektor Makanan dan Minuman Yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2024) - Nessa Devira Oktavia; Ratnawati Raflis (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2025)
This study ams to examine the effect of managerial ownership, profitability, free cash flow, and company size on earnings management in food and beverage manufacturing companies listed on the Indonesia Stoct Exchange (IDX) in 2020-2024. This study is quantitative with secondary data collected through annual financial report documentation from the IDX website and the company’s official website. The study population included 95 food and beverage companies listed on the IDX. The sample selection was conducted using a purposive sampling technique, resulting in 27 companies meeting the research criteria. Data analysis used multiple linear regression with hypothesis testing using SPSS spftware. The t-test result indicate that managerial ownership has a negative and significant effecton earning management, profitability has no significant effect on earning management, free cash flow has a positive and significant effect on earning management, and company size has a positive and significant effect on earning management. Based on the F-test, managerial ownership,profitability, free cash flow, and company size simultaneously have a significant effect on earning managemen in food and beverage companies listed on the IDX. The Adjusted R Square Value 0.770 shows that the four independent variables are able to explain the variation in changes earning management by 77.0%.